Evaluation of local muscle soreness treatment with anterior bite splint made of soft putty impression material - Harry Laksono; Sherman Salim (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Local muscle soreness is the most common temporomandibular disorders complaint of patients seeking treatment in the dental clinics. The emergency treatment that can be done in the clinics to manage this disorder is by making anterior bite splint. Anterior bite splint is usually made of acrylic, but currently there is a soft putty impression material that can also be used for making anterior bite splint. The effectiveness of soft putty anterior bite splint in local muscle soreness treatment still has not clear. Purpose: To determine the effectiveness of the soft putty impression material as a material used for making anterior bite splint in the treatment of local muscle soreness. Case: Six patients was reported five female patients aged 20-40 years old and one male patient aged 37 years old with local muscle soreness. Four female patients with a “click” sound on TMJ. Case management: Make differential diagnosis with screening history (anamnesis), clinical examination consists of extra oral examination such as muscle and temporomandibular joint palpation, measure the mandibular movement, end-feel, load test, intra oral examination and radiographic evaluation. Record the results and make the diagnosis. Make a soft putty anterior bite splint, adjusted and inserted in the maxillary anterior teeth. Record the results based on signs and symptoms. Conclusion: It can be concluded that anterior bite splint made of soft putty impression material is effective for treatment the local muscle soreness.Latar belakang: Salah satu tipe temporomandibular disorders yang paling sering dijumpai di klinik dokter gigi adalah local muscle soreness. Perawatan yang dapat dengan segera dilakukan di klinik untuk mengelola gangguan tersebut adalah dengan pembuatan anterior bite splint. Biasanya anterior bite splint terbuat dari akrilik, namun saat ini telah ada bahan cetak soft putty yang memungkinkan untuk dipakai sebagai bahan pembuatan anterior bite splint. Efektivitas pemakaian anterior bite splint dari bahan putty untuk perawatan local muscle soreness sampai saat ini masih belum jelas. Tujuan: Mengetahui efektivitas pemakaian bahan cetak soft putty sebagai bahan anterior bite splint pada perawatan local muscle soreness. Kasus: Dilaporkan enam pasien terdiri dari lima pasien wanita usia 24-40 tahun dan satu pasien laki-laki usia 37 tahun dengan diagnosis local muscle soreness. Empat pasien wanita disertai suara “klik” pada sendi. Tatalaksana kasus: membuat diagnosis banding dengan anamnesis, pemeriksaan klinis terdiri dari pemeriksaan di luar rongga mulut yang meliputi palpasi otot pengunyahan dan sendi temporomandibular, mengukur pergerakan rahang bawah, end-feel, uji beban, pemeriksaan di dalam rongga mulut dan radiologis. Mencatat hasil pemeriksaannya dan membuat diagnosis. Setelah itu membuat soft putty anterior bite splint dan melakukan penyesuaian dan pemasangan. Mencatat hasilnya berdasarkan keluhan-keluhan dan tanda-tanda. Kesimpulan: Anterior bite splint yang terbuat dari bahan cetak soft putty efektif untuk perawatan local muscle soreness.